Use of virtual reality for symptom management in solid-tumor patients with implications for primary brain tumor research: a systematic review. Issue 5 (28th March 2020) - Leggiero, Nicole M; Armstrong, Terri S; Gilbert, Mark R; King, Amanda L
Abstract: Background: Primary brain tumors (PBTs) remain incurable, with a typically poor prognosis and significant symptom burden for patients. Virtual reality (VR) can potentially alleviate some of the negative aspects of illness by allowing individuals to escape to environments where they can experience more positive thoughts and emotions. Given promising findings for VR use in other clinical populations, there is increasing interest to use VR for symptomatic improvement in oncology patients. The purpose of this review was to analyze the literature of VR-related interventions for symptom management in adult PBT and other solid-tumor patients, which will guide development of future VR interventions in these populations. Methods: A systematic search of EMBASE, PubMed, Scopus, and Web of Science was performed using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines with predefined eligibility criteria. Thirteen studies met the inclusion criteria and were selected for review. Results: Findings showed promising evidence that VR can improve anxiety for solid-tumor patients, with mixed results reported for pain, distress, depression, and mood. There was significant heterogeneity in methodological approaches across the literature and the majority of studies were underpowered and lacked rigorous study designs. Qualitative findings demonstrated a high degree of participant satisfaction with VR use, with very few adverse side effects reported. Conclusions: Findings from this review suggest that VR can be used as an innovative delivery system for targeted interventions to improve symptoms in PBTs and other solid-tumor patient populations, though additional well-designed clinical trials are needed to better establish its efficacy.